The Interplay of Plans and Intentions: A Pledge-Based Intervention to Reduce Participation in a Single Hazardous Event. (November 2019) - Bass, Ellen J.; College, Polly A.; Bruce, Susan
With respect to harm reduction health promotion interventions, consideration of prior plans is critical in evaluating behavior change. This study addresses prior plans on participation in a singular binge drinking occurrence where some students attempt to drink a fifth (750 ml) of liquor as an unsanctioned component of an annual university event. A pledge campaign with incentives was implemented to reduce participation. A link to an anonymous survey was emailed after the event. The campaign was effective as 90.8% of pledgers did not participate in the event. However, those with prior plans to participate were less likely to engage in the campaign. The association of plan commitment, pledge status and participation status was significant (female: X 2 (1)=7.95, p=0.005 and males: X 2 (1)=39.79, p<0.001). Reducing participation for committed students through a pledge campaign alone appears unlikely to change planned behavior. Future research should examine the role of plans and related factors.